The use of selected information skills in the ABS-CBN distance learning center - Marcoleta, Libni M.; Borjal, Wilhelmina G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
This study aimed at determining the extent to which a selected list of technology-based information skills is applied in distance education, with the view of finding out how these skills helped the students cope with the nature and requisites of distance learning process and eventually, to recommend modest inputs in improving this type of academic program.
The study was focused on five (5) selected information skill which provided its conceptual framework, with the teachers/staff and students acting as subjects of the inquiry, i.e. cognitive, locational, selection, selective, and IT skills.
Notwithstanding its limitation, the study succeeded in confirming the fact that by and large, students assign a high premium on the need to know (cognitive) the subject matter and its relevance to their field of interest. This finding was further affirmed by their competence to assess (selection) the information resource, and their ability to accept or reject (selective) the gathered information on account of its use and/or relevance, or none at all.
While the study revealed that students still rely on the stored information in a library when searching for data (locational), there is now an apparent preference in the students' use of technology-based information skills (IT skills) if their increasing use was an indication.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Distance education -- Philippines -- Quezon City; Instructional systems -- Philippines -- Quezon City